Rural Household Access to Assets and Agrarian Institutions : A Cross Country Comparison - Zezza, Alberto (Washington, DC: World Bank, 2012)
Access to assets and agrarian institutions is of critical importance to the economic viability of rural households. Understanding the extent of this access and how it links to the ability of rural households to employ different pathways out of poverty is thus vital for designing rural development policies. This paper characterizes household access to assets and agrarian institutions through the comparative analysis of datasets from 15 nationally representative household surveys from four regions of the developing world. It finds that the access of rural households to a range of assets (including education, land and livestock) and institutions is in general low, though highly heterogeneous across countries, and by categories of households within countries. A large share of rural agricultural households do not use or have access to basic productive inputs, agricultural support services or output markets, and in general it is the landless and the smallest landowners who suffer significantly more from this lack of access.